The effect of load placement on the power production characteristics of three lower extremity jumping exercises - Suchomel, T. J.; McKeever, S. M.; Sijuwade, O.; Carpenter, L.; McMahon, J. J.; Loturco, I.; Comfort, P. (Journal of Human Kinetics, 2019)
The purpose of this study was to compare the power production characteristics of the jump squat (JS), hexagonal barbell jump (HEXJ), and jump shrug (JShrug) across a spectrum of relative loads. Fifteen resistance-trained men completed three testing sessions where they performed repetitions of either the JS, HEXJ, or JShrug at body mass (BM) or with 20, 40, 60, 80, or 100% of their BM. Relative peak power (PPRel), relative force at PP (FPP), and velocity at PP (VPP) were compared between exercises and loads. In addition, power-time curves at each load were compared between exercises. Load-averaged HEXJ and JShrug PPRel were statistically greater than the JS (both p < 0.01), while no difference existed between the HEXJ and the JShrug (p = 1.000). Load-averaged JShrug FPP was statistically greater than both the JS and the HEXJ (both p < 0.001), while no statistical difference existed between the JS and the HEXJ (p = 0.111). Load-averaged JS and HEXJ VPP were statistically greater than the JShrug (both p < 0.01). In addition, HEXJ VPP was statistically greater than the JS (p = 0.009). PPRel was maximized at 40, 40, and 20% BM for the JS, HEXJ, and JShrug, respectively. The JShrug possessed statistically different power-time characteristics compared to both the JS and the HEXJ during the countermovement and propulsion phases. The HEXJ and the JShrug appear to be superior exercises for PPRel compared to the JS. The HEXJ may be considered a more velocity-dominant exercise, while the JShrug may be a more force-dominant one.